Reflecting on Policy Research: Insights on Engagement - Venot, Jean-Philippe (CGIAR Challenge Program on Water and Food, 2013)
Main message Change is not the outcome of a simple “from”(research) “to” (policy) model. It is most likely to take place in the form of incremental adjustments, grounded in daily interactions between stakeholders.